Pengaruh Latar Belakang Pendidikan, Lama Usaha, Dan Pemahaman Pengusaha Umkm Di Kota Bali Terhadap Tingkat Kepatuhan Pemenuhan Kewajiban Perpajakan - Kadek Boby Reza Arya Dana (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the effect of educational background, length of business, and understanding of MSME entrepreneurs on compliance with tax obligations. The subjects in this study were entrepreneurs who were involved in the UMKM business sector in the city of Bali. The number of samples used in this study were 78 respondents. The sampling method used in this study is by using convenience sampling, and the writing technique is done by using quantitative research methods. The data obtained by the researcher were then processed by multiple linear regression method using SPSS software. The results of the above research indicate that the educational background variable does not significantly influence the fulfillment of tax obligations. While the variables of length of business and understanding of MSME entrepreneurs have a significant effect on the fulfillment of tax obligations.